Liquidity of Danish government and covered bonds: Before, during and after the financial crisis. Preliminary findings - Birgitte Vølund Buchholst; Jacob Gyntelberg; Thomas Sangill (Danmarks Nationalbank, 2010)
We present preliminary findings on the liquidity of the government and covered bond markets in Denmark before, during and after the 2008 financial crisis. The analysis focuses on wholesale trading in benchmark bonds in the two markets and is based on an up to now unused transaction level dataset for the period from January 2005 until May 2010. We find that even though trading continued during the crisis, both markets experienced substantial declines in liquidity and significantly increased liquidity risk. Overall, our findings suggest that Danish benchmark covered bonds by and large are as liquid as Danish government bonds during periods of market stress. The findings also suggest that before the crisis government bonds were slightly more liquid than covered bonds in both the short- and longterm market segments. For the period after the crisis, the two markets appear to have had more or less the same level of liquidity for short-term as well as long-term bonds.
Keywords: 330; Öffentliche Anleihe; Pfandbrief; Marktliquidität; Finanzkrise; Dänemark